IMPACT OF HARDENING ON J INTEGRAL AT THE SLIGHTLY CURVED ELASTICITY-PLASTICITY CRACK TIP UNDER QUASI-STATIC LOADS - YANG DaPeng; WANG JunJie; ZHAO Yao; LI TianYun (Jixie qiangdu)
J integral of elastic-plastic curved crack in hardened material under quasi-static loads has been mainly studied,and curved crack tip J integral has been calculated as a practical application of a second order perturbation method and theorem of surname KA,where the effects of quasi-static applied stresses and quasi-static normal and shear stresses on the boundaries of plasticity area are synthetically taken into considerations. Diagrams have been constructed to analyse the transformation relationships between curved crack J integral and hardening exponents. Curved crack J integral will decrease when hardening exponents increase in hardened material. Curved crack J integral decrease extent will be more and more severe when hardening exponents increase evenly. Curved crack J integral will decrease when external loads decrease with the same hardening exponents. A theoretical model where J integral of elastic-plastic curved crack was calculated has been established in hardened material.